Ukraina na początku XX wieku oczami Konstantego Paustowskiego - Bortnowski, Antoni (Studia Rossica Posnaniensia, 2016)
The beginning of 20th century was a very complicated period in the history of the Ukrainian territories. Konstantin Paustovsky spent his youth in the southern part of the Russian Empire and could observe all the historical processes happening to his country. In his autobiography Story of a life Paustovsky presents a very interesting view of Ukraine at the beginning of the 20th century and during the Russian Civil War. The author of this article analyzes Paustovsky’s perception of Ukraine and tries to give an answer to the question of how a descendant of Zaporozhian Cossacks and Polish intellectuals could become a Russian patriot.